Revealing Domain Structure through Linker-Scanning Analysis of the Murine Leukemia Virus (MuLV) RNase H and MuLV and Human Immunodeficiency Virus Type 1 Integrase Proteins - Puglia, Jennifer (American Society for Microbiology, 2006)
Linker-scanning libraries were generated within the 3′ terminus of the Moloney murine leukemia virus (M-MuLV) pol gene encoding the connection-RNase H domains of reverse transcriptase (RT) as well as the structurally related M-MuLV and human immunodeficiency virus type 1 (HIV-1) integrase (IN) proteins. Mutations within the M-MuLV proviral vectors were Tn7 based and resulted in 15-bp insertions. Mutations within an HIV-1 IN bacterial expression vector were based on Tn5 and resulted in 57-bp insertions. The effects of the insertions were examined in vivo (M-MuLV) and in vitro (HIV-1). A total of 178 individual M-MuLV constructs were analyzed; 40 in-frame insertions within RT connection-RNase H, 108 in-frame insertions within IN, 13 insertions encoding stop codons within RNase H, and 17 insertions encoding stop codons within IN. For HIV-1 IN, 56 mutants were analyzed. In both M-MuLV and HIV-1 IN, regions are identified which functionally tolerate multiple-linker insertions. For MuLV, these correspond to the RT-IN proteolytic junction, the junction between the IN core and C terminus, and the C terminus of IN. For HIV-1 IN, in addition to the junction between the IN core and C terminus and the C terminus of IN, insertions between the N terminus and core domains maintained integration and disintegration activity. Of the 40 in-frame insertions within the M-MuLV RT connection-RNase H domains, only the three C-terminal insertions mapping to the RT-IN proteolytic junction were viable. These results correlate with deletion studies mapping the domain and subdomain boundaries of RT and IN. Importantly, these genetic footprints provide a means to identify nonessential regions within RT and IN for targeted gene therapy applications.